2012
DOI: 10.1007/s12307-012-0126-7
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Microenvironment and Myeloid-Derived Suppressor Cells

Abstract: Tumor progression has been demonstrated to be supported by chronic inflammatory conditions developed in the tumor microenvironment and characterized by the longterm secretion of various inflammatory soluble factors (including cytokines, chemokines, growth factors, reactive oxygen and nitrogen species, prostaglandins etc.) and strong leukocyte infiltration. Among leukocytes infiltrating tumors, myeloid-derived suppressor cells (MDSCs) represent one of the most important players mediating immunosuppression. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(88 citation statements)
references
References 120 publications
1
80
0
4
Order By: Relevance
“…the respective tumor vasculature (18,19). In addition, they regulate activation, maintenance, and activity of antigen-specific TCs through a plethora of immune-modulatory mechanisms, involving recruitment of immune-suppressive cell populations, particularly Tregs, MDSCs, or mast cells, among others; secretion of immune-suppressive cytokines, such as TGF-β1; or expression of immune-modulatory ligands, such as PDL-1 (19)(20)(21)(22)(23)(24)(25). Regulation of TC activity in situ occurs at interindividually varying levels, and indeed, Koch et al were able to demonstrate the tumor-selective activation and cytotoxic activity in situ of small, individually varying subpopulations of CD8 + TCs in CRC (14).…”
Section: Tnf-α Expression Is Restricted To Activated Tumor-infiltratimentioning
confidence: 99%
“…the respective tumor vasculature (18,19). In addition, they regulate activation, maintenance, and activity of antigen-specific TCs through a plethora of immune-modulatory mechanisms, involving recruitment of immune-suppressive cell populations, particularly Tregs, MDSCs, or mast cells, among others; secretion of immune-suppressive cytokines, such as TGF-β1; or expression of immune-modulatory ligands, such as PDL-1 (19)(20)(21)(22)(23)(24)(25). Regulation of TC activity in situ occurs at interindividually varying levels, and indeed, Koch et al were able to demonstrate the tumor-selective activation and cytotoxic activity in situ of small, individually varying subpopulations of CD8 + TCs in CRC (14).…”
Section: Tnf-α Expression Is Restricted To Activated Tumor-infiltratimentioning
confidence: 99%
“…Previous studies have demonstrated that tumor-infiltrating myeloid progenitors such as monocytes are immune-suppressive (41,42). Flow cytometry analysis revealed that tumor-infiltrating monocytic cells (Gr-1+ CD11b+) from MB49 CD14-high tumors have significantly reduced expression of MHC II, indicating possible impairment in antigen presentation to CD4 T cells (Fig.…”
Section: Cd14-mediated Signaling Is Required For Il6 Production and Lmentioning
confidence: 85%
“…Evidence supporting a role for MDSCs in modulating MAGE-A4 expression is provided by the results of the assessment of LLC tumor cell proliferation, which demonstrated that MDSC supernatant was able to promote the growth of tumor cells and induce increased expression of MAGE-A4. MDSCs secrete multiple factors that may support the growth and survival of tumor cells (39)(40)(41)(42), and it would be of interest to confirm whether MDSCs secrete soluble factors that regulate MAGE-A4 expression. In further support of this, it has previously been reported that CT antigen expression is association with cell cycle progression and proliferation (43)(44)(45), apoptosis (13) and susceptibility of cancer cells to cytokines (46), suggesting that the CT antigen itself may be associated with prognosis.…”
Section: Discussionmentioning
confidence: 99%